Highly compacted high-capacity negative electrode material and preparation method and use thereof
Patent Information
- Application Number
- CN202310670338.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-06-07
AI Technical Summary
但是,各向同性生焦石墨化程度低,作为锂离子电池负极材料使用时的压实密度和比容量很难满足要求
[0036]本发明提供了一种高压实高容量负极材料及其制备方法和用途。本发明通过将大块状的各向同性生焦在750~790℃进行高温煅烧获得小域结构占比显著提高的煅后焦,这些小域结构在随后的石墨化过程中石墨化程度高,能够显著提高负极材料的压实密度和比容量。本发明通过包覆重质沥青和/或添加导电剂的复合沥青,这些二次喹啉不溶物和/或导电剂的存在使沥青焦化在晶核的作用下容易较早且较多地生成小球体,并阻碍中间相小球体的长大与融并,有利于生成细镶嵌结构多的各向同性焦包覆层,这些细镶嵌结构在随后的石墨化过程中石墨化程度低,石墨层晶面间距(d002)较大,与电解液的相容性好,在充放电循环过程中石墨层难剥离,能够显著提高负极材料的循环性能。通过控制内核和外壳的各向同性度和石墨化程度,能最大程度的保持所述负极材料在使用过程中的电学性能参数处于最佳状态。
Smart Images

Figure BDA0004272729860000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery anode material technology, and in particular to a high-pressure, high-capacity anode material, its preparation method, and its applications. Background Technology
[0002] Energy storage technology is an effective means to balance various energy application demands and improve the overall energy efficiency of society. It has broad application prospects in areas such as improving the access capacity of large-scale and distributed renewable energy sources and enhancing the power quality of urban microgrids. Among existing energy storage battery systems, lithium-ion batteries have become the most popular due to their flexible material system and rapid technological updates, and have been widely used in various demonstration projects. Isotropic green coke is a coke-like material with an isotropic or mosaic optical structure. After graphitization, it can be used to prepare long-life lithium-ion battery anode materials. However, isotropic green coke has a low degree of graphitization, making it difficult to meet the requirements for compaction density and specific capacity when used as a lithium-ion battery anode material. Therefore, how to improve the compaction density and specific capacity of anode materials prepared from isotropic green coke to meet the needs of the energy storage field while maintaining the long lifespan is an urgent problem that researchers need to solve. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention provides a high-compact, high-capacity anode material, its preparation method, and its applications. The preparation method for this anode material is simple, and the resulting anode material exhibits high compaction, high capacity, and long cycle life.
[0004] The objective of this invention is achieved through the following technical solution:
[0005] A method for preparing a negative electrode material, the method comprising the following steps:
[0006] (1) Calcining isotropic raw coke under a protective atmosphere to obtain calcined coke;
[0007] (2) The calcined coke obtained in step (1) is crushed, shaped and sieved to obtain coke powder;
[0008] (3) The coke powder obtained in step (2) is mixed with pitch and then calcined, cooled to room temperature, and then graphitized to prepare the negative electrode material.
[0009] According to an embodiment of the present invention, the negative electrode material is an artificial graphite negative electrode material.
[0010] According to an embodiment of the present invention, in step (1), the isotropic coke is isotropic petroleum coke and / or isotropic pitch coke.
[0011] According to an embodiment of the present invention, in step (1), the optical structure of the isotropic focusing is a state in which a mosaic structure and a small-domain structure coexist. The mosaic structure refers to a structure in which the size of the same-color region in the polarized image is ≤5μm, and the small-domain structure refers to a structure in which the size of the same-color region in the polarized image is between 5 and 8μm. The proportion of the small-domain structure in the isotropic focusing is ≤40%.
[0012] According to an embodiment of the present invention, in step (1), the average particle size of the isotropic coke is ≥1cm, for example 2 to 15cm, such as 4cm, 5cm, 6cm, 7cm, 8cm, 9cm or 10cm.
[0013] According to an embodiment of the present invention, in step (1), the calcination temperature is 750–790°C, exemplarily 750°C, 755°C, 760°C, 765°C, 770°C, 775°C, 780°C, 785°C, or 790°C. The calcination time is 1–6 hours, for example 2–5 hours, exemplarily 4 hours or 6 hours. The protective atmosphere is, for example, a nitrogen atmosphere or an argon atmosphere. Further, after calcination, the obtained product is allowed to cool naturally to room temperature to obtain calcined coke.
[0014] According to an embodiment of the present invention, in step (1), the calcined coke is an isotropic coke with an optical structure in which a mosaic structure and a small-domain structure coexist. The mosaic structure refers to a structure with a color region size ≤ 10 μm in a polarized image, and the small-domain structure refers to a structure with a color region size between 10 and 20 μm in a polarized image. The proportion of small-domain structures in the calcined coke is ≥ 60%. The significantly increased proportion of small-domain structures in the calcined coke indicates that the high-temperature calcination process of the isotropic green coke at 750–790°C is beneficial to the rearrangement and growth of its internal small-domain structures, thereby increasing the compaction density and specific capacity of the negative electrode material.
[0015] According to an embodiment of the present invention, in step (2), the average particle size of the coke powder is 10-20 μm, preferably 12-17 μm, for example 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or 17 μm.
[0016] According to an embodiment of the present invention, in step (2), the pulverization can be carried out using micro-powder pulverizing equipment known in the art, such as an impact pulverizer, an airflow vortex pulverizer, an ultra-micro ball mill, or a pendulum mill.
[0017] According to an embodiment of the present invention, in step (2), the shaping can be performed using equipment known in the art, such as an airflow vortex pulverizer.
[0018] According to an embodiment of the present invention, in step (2), the screening can be performed using equipment known in the art, such as a vibrating screen.
[0019] According to an embodiment of the present invention, in step (3), the mass ratio of coke powder to asphalt is 100:(5-10), for example, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10.
[0020] According to an embodiment of the present invention, in step (3), the asphalt is selected from heavy asphalt with a secondary quinoline content ≥10%; and / or, the asphalt is selected from composite asphalt with a secondary quinoline content ≤1% and a conductive agent.
[0021] The conductive agent is selected from at least one of carbon black, graphene oxide, and carbon nanotubes. The conductive agent accounts for 8-15% of the total mass of the composite asphalt.
[0022] According to an embodiment of the present invention, in step (3), the calcination is carried out by heating to 410-450°C at a rate of 20-30°C / min, then heating to 480-520°C at a rate of 30-40°C / h, holding at that temperature for 1-8 hours, and then cooling to room temperature. The calcination is carried out under a protective atmosphere, such as a nitrogen atmosphere or an argon atmosphere.
[0023] According to an embodiment of the present invention, in step (3), the temperature of the graphitization treatment is 2600-3000℃, preferably 2800℃; the time of the graphitization treatment is 5-24 hours, preferably 6-12 hours.
[0024] The present invention also provides a negative electrode material prepared by the above method.
[0025] According to an embodiment of the present invention, the negative electrode material has a core-shell coated structure, wherein the core is graphite with a graphitization degree of 92% to 96% and an isotropic degree of ≥96%, and the outer shell is graphite with a graphitization degree of 86% to 90% and an isotropic degree of 100%.
[0026] According to embodiments of the present invention, the graphitization degree of the core graphite is 92%, 93%, 94%, 95%, or 96%. The graphitization degree of the outer shell graphite is 86%, 87%, 88%, 89%, or 90%.
[0027] According to embodiments of the present invention, the isotropy of the core graphite is 96%, 97%, 98%, 99%, or 100%.
[0028] According to an embodiment of the present invention, the thickness of the outer shell is 200-500 nm.
[0029] According to an embodiment of the present invention, the mass of the secondary quinoline compound and / or conductive agent in the shell accounts for 8% to 20% of the total mass of the shell, for example, 8%, 10%, 12%, 15%, 18% or 20%.
[0030] According to an embodiment of the present invention, the compaction density of the negative electrode material is ≥1.54 g / cc.
[0031] According to an embodiment of the present invention, the specific capacity of the negative electrode material is ≥350mAh / g.
[0032] According to an embodiment of the present invention, the negative electrode material retains ≥96% of its capacity after 3000 cycles at room temperature (0.1°C).
[0033] The present invention also provides the application of the above-mentioned negative electrode material in lithium-ion batteries.
[0034] The present invention also provides a lithium-ion battery, the lithium-ion battery including a negative electrode, the negative electrode including the above-described negative electrode material.
[0035] The beneficial effects of this invention are:
[0036] This invention provides a high-compact, high-capacity anode material, its preparation method, and its applications. The invention obtains calcined coke with a significantly increased proportion of small-domain structures by high-temperature calcination of bulk isotropic green coke at 750–790°C. These small-domain structures exhibit high graphitization during subsequent graphitization, significantly improving the compaction density and specific capacity of the anode material. The invention also utilizes a coating of heavy asphalt and / or composite asphalt with added conductive agents. The presence of these secondary quinoline insolubles and / or conductive agents facilitates the early and abundant formation of small spherical particles during asphalt coking under the influence of crystal nuclei, hindering the growth and coalescence of mesophase spherical particles. This promotes the formation of an isotropic coke coating layer with numerous fine mosaic structures. These fine mosaic structures exhibit low graphitization during subsequent graphitization, resulting in a low interplanar spacing (d) between graphite layers. 002 The graphite layer has a large internal density and good compatibility with the electrolyte. It is also difficult to peel off during charge-discharge cycles, which significantly improves the cycle performance of the negative electrode material. By controlling the isotropy and graphitization degree of the core and shell, the electrical performance parameters of the negative electrode material can be maintained at their optimal state during use.
[0037] The negative electrode material prepared by this invention, when used in lithium-ion batteries, simultaneously exhibits high capacity, high compaction, and long cycle life. Furthermore, the preparation process of this invention is simple, highly practical, and can meet the needs of both high-end energy storage and low-end lithium-ion power batteries. Detailed Implementation
[0038] The preparation method of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0039] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0040] Example 1
[0041] Isotropic petroleum coke (D) 50 The coke (5 cm in diameter) was calcined at 750℃ under a nitrogen atmosphere for 6 hours, and then cooled to obtain calcined coke. After pulverizing in an impact crusher, it was shaped and sieved to obtain an average particle size D. 50 The coke powder has a thickness of 14 μm. 100 g of coke powder was mixed with 10 g of heavy pitch (containing 12% secondary quinoline compounds) and placed in a high-temperature furnace, then nitrogen gas was introduced. The temperature was first rapidly increased to 420 °C at a rate of 25 °C / min, then slowly increased to 520 °C at a rate of 35 °C / h, held at that temperature for 3 hours, and then cooled to room temperature. It was then graphitized at 2800 °C for 10 hours and cooled to obtain the anode material. The graphitization degree of the core graphite was 96%, and the isotropy was 97%; the graphitization degree of the outer shell graphite was 86%, and the isotropy was 100%. The outer shell thickness was 300 nm, and the secondary quinoline compound content in the shell was 12%.
[0042] Example 2
[0043] Isotropic petroleum coke (D) 50 The coke (5 cm in diameter) was calcined at 790℃ under a nitrogen atmosphere for 2 hours, and then cooled to obtain calcined coke. After pulverizing in an impact crusher, it was shaped and sieved to obtain an average particle size D. 50 The coke powder has a thickness of 15 μm. 100 g of coke powder was mixed with 6 g of pitch (10% carbon black content) and placed in a high-temperature furnace, then nitrogen gas was introduced. The temperature was first rapidly increased to 430 °C at a rate of 20 °C / min, then slowly increased to 500 °C at a rate of 30 °C / h, held at that temperature for 5 hours, and then cooled to room temperature. It was then graphitized at 3000 °C for 6 hours and cooled to obtain the anode material. The graphitization degree of the core graphite was 92%, and the isotropy was 99%; the graphitization degree of the outer shell graphite was 90%, and the isotropy was 100%. The thickness of the outer shell was 400 nm, and the carbon black content in the shell layer was 10%.
[0044] Example 3
[0045] Isotropic petroleum coke (D) 50The coke (8 cm in diameter) was calcined at 780℃ under a nitrogen atmosphere for 3 hours, and then cooled to obtain calcined coke. After pulverizing in an impact crusher, it was shaped and sieved to obtain an average particle size D. 50 The coke powder has a thickness of 17 μm. 100 g of coke powder was mixed with 8 g of pitch (8% graphene oxide content) and placed in a high-temperature furnace, then nitrogen gas was introduced. The temperature was first rapidly increased to 450 °C at a rate of 26 °C / min, then slowly increased to 510 °C at a rate of 35 °C / h, held at that temperature for 4 hours, and then cooled to room temperature. It was then graphitized at 2800 °C for 12 hours and cooled to obtain the anode material. The graphitization degree of the core graphite was 94%, and the isotropy was 98%; the graphitization degree of the outer shell graphite was 88%, and the isotropy was 100%. The thickness of the outer shell was 350 nm, and the graphene content in the shell was 8%.
[0046] Comparative Example 1
[0047] Isotropic petroleum coke (D) 50 The coke (5 cm in diameter) was calcined at 1200℃ under a nitrogen atmosphere for 6 hours, and then cooled to obtain calcined coke. After pulverizing in an impact crusher, it was shaped and sieved to obtain an average particle size D. 50 The coke powder has a thickness of 14 μm. 100 g of coke powder was mixed with 10 g of heavy pitch (containing 12% secondary quinoline compounds) and placed in a high-temperature furnace, then nitrogen gas was introduced. The temperature was first rapidly increased to 420 °C at a rate of 25 °C / min, then slowly increased to 520 °C at a rate of 35 °C / h, held at that temperature for 3 hours, and then cooled to room temperature. It was then graphitized at 2800 °C for 10 hours and cooled to obtain the anode material. The graphitization degree of the core graphite was 98.6%, and the isotropy was 86%; the graphitization degree of the outer shell graphite was 86%, and the isotropy was 100%. The outer shell thickness was 300 nm, and the secondary quinoline compound content in the shell was 12%.
[0048] Comparative Example 2
[0049] Isotropic petroleum coke (D) 50 After being pulverized in an impact crusher (with a particle size of 5cm), the particles are shaped and sieved to obtain an average particle size D. 50Coke powder with a thickness of 14 μm was calcined at 750 °C under a nitrogen atmosphere for 6 hours, and then cooled to obtain calcined coke. 100 g of calcined coke was mixed with 10 g of heavy pitch (containing 12% secondary quinoline compounds) and placed in a high-temperature furnace, then nitrogen was introduced. The temperature was first rapidly increased to 420 °C at a rate of 25 °C / min, then slowly increased to 520 °C at a rate of 35 °C / h, held at that temperature for 3 hours, and then cooled to room temperature. It was then graphitized at 2800 °C for 10 hours and cooled to obtain the anode material. The graphitization degree of the core graphite was 90%, and the isotropy was 100%; the graphitization degree of the outer shell graphite was 86%, and the isotropy was 100%. The outer shell thickness was 300 nm, and the secondary quinoline compound content in the shell layer was 12%.
[0050] Electrochemical performance testing
[0051] Half-cell testing method: The negative electrode materials prepared in Examples 1-3 and Comparison 1-2 were mixed evenly with conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) in a mass ratio of 95:1:1.5:2.5. The mixture was then coated onto copper foil, and the coated electrode was dried in a vacuum drying oven at 120°C for 12 hours. Simulated battery assembly was performed in an argon-protected Braun glove box. The electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1), and lithium metal sheets were used as the counter electrode. Simulated battery testing was conducted in a 5V, 10mA Xinwei battery test cabinet. The charge / discharge voltage was 0.01–1.5V, and the charge / discharge rate was 0.1C. The initial reversible capacity obtained from the tests is listed in Table 1.
[0052] Full cell test method: Using the negative electrode materials prepared in Examples 1-3 and Comparison 1-2 as negative electrodes, lithium iron phosphate as positive electrodes, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution as electrolyte, full cells were assembled and charged and discharged at room temperature at 0.1C, with a voltage range of 3.0-4.2V. The cycle performance obtained from the test is listed in Table 1.
[0053] Table 1. Electrochemical performance test results
[0054]
[0055] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material, the method comprising the following steps: (1) Calcining isotropic raw coke under a protective atmosphere to obtain calcined coke; (2) The calcined coke obtained in step (1) is crushed, shaped and sieved to obtain coke powder; (3) The coke powder obtained in step (2) is mixed with pitch and then calcined, cooled to room temperature, and then graphitized to prepare the negative electrode material. In step (1), the optical structure of the isotropic focusing is a state in which a mosaic structure and a small-domain structure coexist. The mosaic structure refers to a structure in which the size of the same color region in the polarized image is ≤5μm, and the small-domain structure refers to a structure in which the size of the same color region in the polarized image is between 5 and 8μm. The proportion of the small-domain structure in the isotropic focusing is ≤40%. In step (1), the forged coke is an isotropic coke with an optical structure in which a mosaic structure and a small-domain structure coexist. The mosaic structure refers to a structure in which the size of the same color region in the polarized image is ≤10μm, and the small-domain structure refers to a structure in which the size of the same color region in the polarized image is between 10 and 20μm. The proportion of the small-domain structure in the forged coke is ≥60%. In step (1), the calcination temperature is 750~790℃; the calcination time is 1~6 hours; and the protective atmosphere is a nitrogen atmosphere or an argon atmosphere. In step (1), the average particle size of the isotropic coke is 2~15cm; In step (2), the average particle size of the coke powder is 10~20μm; In step (3), the asphalt is selected from heavy asphalt with a secondary quinoline content ≥10%; and / or, the asphalt is selected from asphalt with a secondary quinoline content ≤1% and a conductive agent as a composite asphalt. In step (3), the calcination is carried out by heating the temperature to 410-450°C at a rate of 20-30°C / min, then heating it to 480-520°C at a rate of 30-40°C / h, maintaining the temperature for 1-8 hours, and then cooling it to room temperature.
2. The preparation method according to claim 1, wherein, In step (1), the isotropic raw coke is isotropic petroleum raw coke and / or isotropic pitch raw coke.
3. The preparation method according to claim 1, wherein, In step (3), the mass ratio of coke powder to asphalt is 100:(5-10).
4. The preparation method according to claim 1, wherein, In step (3), the temperature of the graphitization treatment is 2600~3000℃; the time of the graphitization treatment is 5~24 hours.
5. The negative electrode material prepared by the preparation method according to any one of claims 1-4.
6. The negative electrode material according to claim 5, wherein, The negative electrode material has a core-shell coated structure, with the core being graphite with a graphitization degree of 92%~96% and an isotropic degree of ≥96%, and the outer shell being graphite with a graphitization degree of 86%~90% and an isotropic degree of 100%.
7. The negative electrode material according to claim 6, wherein, The thickness of the outer shell is 200~500nm.
8. The negative electrode material according to claim 6, wherein, The mass of secondary quinoline compounds and / or conductive agents in the shell accounts for 8-20% of the total mass of the shell.
9. The application of the negative electrode material according to any one of claims 5-8 in lithium-ion batteries.
10. A lithium-ion battery, the lithium-ion battery comprising a negative electrode, the negative electrode comprising the negative electrode material according to any one of claims 5-8.
Citation Information
Patent Citations
Artificial graphite composite negative electrode material for lithium ion battery as well as preparation method and application of artificial graphite composite negative electrode material
CN114597361A
Preparation method of energy-storage long-circulation graphite negative electrode material
CN115477301A